2008
DOI: 10.1037/a0011618
|View full text |Cite
|
Sign up to set email alerts
|

Let your preference be your guide? Preferences and choices are more tightly linked for North Americans than for Indians.

Abstract: Using experimental paradigms from economics and social psychology, the authors examined the cross-cultural applicability of 3 widely held assumptions about preference and choice: People (a) recruit or construct preferences to make choices; (b) choose according to their preferences; and (c) are motivated to express their preferences in their choices. In 6 studies, they compared how middle-class North American and Indian participants choose among consumer products. Participants in both contexts construct nonrand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
223
2
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(237 citation statements)
references
References 88 publications
8
223
2
1
Order By: Relevance
“…This suggests that, even if the production of affiliative expressions may mean hard work for AS participants, it may have long-term social consequences for them and may thus be worth the effort. Arguably, affiliation skills are of particular importance in today's Western societies, where friendships are increasingly determined by individual choice and thus regularly formed around likability and mutual positive affect [34,40,47,76,78,79,104]. Furthermore, as recently suggested by [27], there is a vicious cycle of social exclusion and social incompetence, which may even be "sufficient to cause some individuals to cross the line from subthreshold eccentricity into difficulties in living that register as clinically significant" (p. 84)-something that could explain the increase of the number of individuals diagnosed with autism spectrum disorder in our modern Western societies.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that, even if the production of affiliative expressions may mean hard work for AS participants, it may have long-term social consequences for them and may thus be worth the effort. Arguably, affiliation skills are of particular importance in today's Western societies, where friendships are increasingly determined by individual choice and thus regularly formed around likability and mutual positive affect [34,40,47,76,78,79,104]. Furthermore, as recently suggested by [27], there is a vicious cycle of social exclusion and social incompetence, which may even be "sufficient to cause some individuals to cross the line from subthreshold eccentricity into difficulties in living that register as clinically significant" (p. 84)-something that could explain the increase of the number of individuals diagnosed with autism spectrum disorder in our modern Western societies.…”
Section: Discussionmentioning
confidence: 99%
“…One could achieve greater differentiation by joining smaller groups, distinguishing oneself from other in-group members, or differentiating one's group more from outgroups. Furthermore, research suggests that choice may not be as strongly linked to identity in all cultural contexts (Kim and Drolet 2003;Savani, Markus, and Conner 2008;Stephens, Markus, and Townsend 2007). Examining the degree to which these motivations exist in various cultural contexts, as well as how they combine to drive choice, may provide insight not only into differentiation itself but also the communication of identity across cultures and the integration of multiple motives more broadly.…”
Section: Directions For Future Research and Marketing Implicationsmentioning
confidence: 99%
“…Second, previous studies have reported significant differences in perception and ways of thinking between western and Asian cultures (Cairney and Sless, 1982;Wu and Keysar, 2007;Savani et al, 2008;Falk et al, 2009). For example, East Asians have been found to differ in their choice making from Americans: slower to make choices, less likely to choose according to their preferences, and less motivated to express their preferences in their choices (Savani et al, 2008). Cairney and Sless (1982) also found that Australians and Vietnamese demonstrated different recognition and recall with regard to industrial-safety signs.…”
Section: J Ergon Soc Koreamentioning
confidence: 95%
“…Therefore, it will be good if the introduced water-sport prohibitive signs can convey their intended information to the beachgoers regardless of their nationalities, which is to say the signs should be culture-independent, or culturally compatible (Galdo, 1990). Second, previous studies have reported significant differences in perception and ways of thinking between western and Asian cultures (Cairney and Sless, 1982;Wu and Keysar, 2007;Savani et al, 2008;Falk et al, 2009). For example, East Asians have been found to differ in their choice making from Americans: slower to make choices, less likely to choose according to their preferences, and less motivated to express their preferences in their choices (Savani et al, 2008).…”
Section: J Ergon Soc Koreamentioning
confidence: 98%